Study of Communication Network Travel-Related eWOM on Instagram Social Media - Bhadrika Grahita Nandiwardhana; Bayu Indra Pratama; Dian Tamitiadini (Jurnal Pekommas, 2019)
The research is about analysis of communication network to travel-related EWOM IN social media Instagram on account  @exploremalang which researcher want to know how characteristic of network system formed and the usual messages in travel-related EWOM on account @exploremalang in Instagram. Paradigm which used is Post-positivism by unobtrusive methods data in collection data. The research used communication network analysis method and content analysis to know content of messages common said by actors, and how intimacy actors in the form of a travel-related eWOM.  Result of the research found structure of communication network in the form of global network Radial personal network from four photos which selected by researcher. Measurement showed cohesiveness in this network is low. Measurement of degree, betweeness and closeness dominated by actors who often mentions other actors. Then, obtained interlocking personal network click formed. Meanwhile structure of network, researcher also found sixth characteristic of travel-related EWOM.